Antioxidant Activity In Vitro of N‐(1‐deoxy‐α‐d‐xylulos‐1‐yl)‐Phenylalanine: Comparison Among Maillard Reaction Intermediate, End‐Products and Xylose‐Phenylalanine. Issue 5 (3rd April 2019) - Cui, Heping; Hayat, Khizar; Zhang, Xiaoming
Abstract: The Maillard reaction end‐products (MRPs) and intermediate (MRI, N ‐(1‐deoxy‐α‐D‐xylulos‐1‐yl)‐phenylalanine) derived from xylose (Xyl) and phenylalanine (Phe) model system were synthesized in an aqueous medium, and their antioxidant activity was evaluated. Both the MRPs and N ‐(1‐deoxy‐α‐d ‐xylulos‐1‐yl)‐phenylalanine exhibited the Fe 2+ chelating activity at their addition concentration of 2 to 12 mg/mL. While their reducing power, free radical scavenging activity, and inhibition effect on lipid peroxidation were observed at a lower addition concentration of only 0.2 to 1.2 mg/mL. The free radical scavenging activity was improved with the increase in their concentration, and a time‐dependent scavenging effect of the MRI was also shown in the results. However, a weak chelating activity of Xyl‐Phe on Fe 2+ in a concentration‐dependent manner was observed, but no significant free radical scavenging activity or reducing power of Xyl‐Phe was found. Based on these results, possible free radical scavenging pathway of the MRI was proposed. As the MRI showed lower antioxidant activity than MRPs, the application of the MRI in combination with MRPs as an antioxidant was proposed in cooked or semi‐processed foods to avoid the deterioration induced by oxidation. Practical Application: The Maillard reaction intermediates (MRIs) showed antioxidant activity and could be applied in foods as both antioxidants and flavor enhancer. The MRIs will probably extend the shelf‐life of lipid rich foods and could be the substitute of artificial antioxidants.